PENDAPATAN DAN KETAHANAN PANGAN RUMAH TANGGA PETANI PADI DI DESA RAWAN PANGAN - Ega Noveria Putri Hernanda; Yaktiworo Indriani; Umi Kalsum (Lampung University, 2017)
This study aims to analyze the amount of rice farming income, food expenditure and food security of rice farmer households (HH), and factors related to food security. The location of this study is choosen purposively in Sukamarga Village, Buay Pematang Ribu (BPR) Ranau Tengah Subdistrict, South Ogan Komering Ulu (OKU) Regency in which respondents of this research are 66 rice farmer households. Data of this research were collected in January – March 2016 and analyzed by using descriptive qualitative analysis and quantitative using corelation of Pearson product moment analysis. The results showed that the average income of rice farming per ha was Rp6,936,134.19 in wet season and Rp6,716,552.06 in dry season. The average total household income was Rp2,427,513.67 per month. The evaluation on households’ food security showed that there were 20 HHs in food secure category, 25 HHs in lack of food, 11 HH in vulnerable food, and 10 HHs in food insecure. The factors related to food security were income, land area, rice production, the amount of household members, husband education’s level, and food expenditure. Key words: food expenditure, food security, income